Precipitation over the Southern Ocean: properties and formation mechanisms - Luís, Diogo da Silva (2022)
Uncertainty in Southern Ocean/Antarctica precipitation estimates is high due to the lack of measurements to evaluate model and reanalysis products performance. Unique precipitation measurements were carried out during the Swiss Polar Institute’s Antarctic Circumnavigation Expedition (ACE) (December 2016 - March 2017). High temporal resolution measurements of precipitation were performed by a Snow Particle Counter (SPC) and by a Micro Rain Radar (MRR) aboard the RV Akademik Tryoshnikov. Radiosondes were launched periodically to observe the vertical structure of the atmosphere. Additionally, MRR and radiosonde measurements from Dumont D’Urville station (DDU) were available when the expedition was in the Mertz Glacier region. In this work, the snowfall observed during ACE was analysed. Two distinct snowfall events that occurred during the ACE campaign were chosen to evaluate ECMWF’s ERA5 reanalysis product and AMPS (Antarctic Mesoscale Prediction System using Polar-WRF model). The first event on 2 February 2017 was associated with an extratropical cyclone east of Adélie Land and a moderate along-shore moisture transport. The second event on 8-10 February 2017 was associated with a cyclone west of Mertz blocked by a high-pressure ridge, directing a strong moisture transport (classified as an atmospheric river) towards Adélie Land with precipitation affecting the coastal region. The precipitation amount and phase, as well as vertical profiles, are analysed using observations, and compared to the model and reanalysis data.